Stimulatory Effect of Allantoin on Imidazoline I1 Receptors in Animal and Cell Line - Yang, T. T.; Chiu, N. H.; Chung, H. H.; Hsu, C. T.; Lee, W. J.; Cheng, J.-T. (Hormone and Metabolic Research, 2012)
Allantoin is known as the agonist of imidazoline receptor, especially the I2 subtype. Effect of allantoin on imidazoline I1 receptor (I1R) relating to reduction of blood pressure and its merit in steatosis are still obscure. Also, farnesoid X receptor (FXR) plays an important role in lipid homeostasis related to I1R activation. Thus, we administered allantoin into high fat diet (HFD)-fed mice showing hypertriglyceridemia and hypercholesterolemia. Allantoin significantly improved hyperlipidemia in HFD mice after 4 weeks of administration. Pretreatment with efaroxan, at a dose sufficient to inhibit I1R activation, attenuated the action of allantoin. In addition, in cultured HepG2 cells, allantoin increased the expression of farnesoid X receptor (FXR). The allantoin-induced FXR expression was blocked by efaroxan. Similar changes were observed in the expressions of FXR-targeted genes. Otherwise, allantoin also lowered systolic blood pressure (SBP) in HFD mice that can be blocked by efaroxan. Taken together, allantoin has an ability to activate I1R for improvement of metabolic disorders.
Keywords: allantoin; blood pressure; efaroxan; farnesoid X receptor (FXR); imidazoline receptor; steatosis